DILEMA PRIORITAS: ANALISIS PERUBAHAN KEBIJAKAN LUAR NEGERI BRAZIL ERA BOLSONARO DALAM ISU LINGKUNGAN GLOBAL - Nurul Husna (Journal of International Relations Diponegoro, 2022)
Changes within Brazil's policy orientation in the environmental sector have been felt since the leadership of President Lula da Silva (2003-2011), then Dilma Roussef (2011-2016), until the realization of the changes was very tangible during the reign of Jair Bolsonaro (2018-present). Bolsonaro's campaign that said if he is elected he will retrack Brazil's environmental policy away from the Paris Agreement has become a huge controversy in the the world. Not to mention that during his reign, changes in domestic and international environmental policies continued to occur. Starting from the merger of environmental management agencies in the Ministry, reducing the allocation of funds for the environment, expanding commercial land in the Amazon Forest, loosening the law for development on Amazon Forest land, up until the creation of many new development projects which being carried out on Amazon Forest land. Various policy changes and the commercialization of land under Bolsonaro's government caused the amount of deforestation in Brazil to increase every year and Brazil's compliance with the provisions of the Paris Agreement decreased. This study uses Hermann's Theory to analyze the causes of changes in policy orientation that occurred in Brazil under Bolsonaro's government. Based on the research that has been done, it is evident that there are two main factors causing the change in policy orientation which are rooted in the leadership factor (Leader Driven) and the Bureaucratic Advocacy factor (Beraucratic Advocacy) from the Bolsonaro government itself.